2010
DOI: 10.4238/vol9-1gmr753
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between glutathione S-transferase polymorphisms and primary glioma in a case-control study in Rio de Janeiro

Abstract: ABSTRACT. The glutathione S-transferases (GSTs), a family of phase II isozymes, detoxify several carcinogens. Genetic variations in GSTs have been associated with increased risk for cancer due to a heritable deficiency in detoxification pathways for environmental carcinogens. Conflicting findings have been reported about the association between constitutive GST polymorphisms and gliomas in different populations. The present case-control study examined 78 patients with primary glioma and 347 controls from Rio d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…In addition, a study of 78 patients and 374 controls did not reveal an association between GST polymorphisms and primary glioma risk in Brazilians (Coutinho et al, 2010). In this study, GSTM1 deletion was not significantly correlated (P = 0.19) with the occurrence of malignant glioma in adult Brazilians.…”
Section: Discussioncontrasting
confidence: 73%
“…In addition, a study of 78 patients and 374 controls did not reveal an association between GST polymorphisms and primary glioma risk in Brazilians (Coutinho et al, 2010). In this study, GSTM1 deletion was not significantly correlated (P = 0.19) with the occurrence of malignant glioma in adult Brazilians.…”
Section: Discussioncontrasting
confidence: 73%
“…Number of female smokers was very less, so it was not possible to compare the results between both the genders. No significant differences were observed between smokers and non-smokers, alcoholic and non-alcoholic individuals, tobacco chewers and non-chewers, carrying homozygous GSTM1/GSTT1/GSTM1T1 null genotype (p>0.05) ( Anantharaman, 2007;Buch et al, 2002;Nair et al, 1999 South Indians c 1744 485 (27.8)** 242 (13.9) 136 (7.8) Naveen et al, 2004;Samson, 2007;Shehnaz et al, 2011;Sreelekha et al, 2001;Suneetha, 2011;Vettriselvi et al, 2006;Vijayalakshmi et al, 2005 East Indians d 67 18(27.0) 9 (13.0) Sikdar et al, 2005 Central Indians e 282 99 (35.1) 37 (13.0) Devi et al, 2008 North Nair et al, 1999;Singh et al, 2009 Blacks b 3008 960 (31.9) 744 (24.9)* 298 (9.9)* Adams et al, 2003;Benzamin et al, 2011;Coutinho et al, 2010;Dandara et al, 2002;Lavender et al, 2009;Masimirembwa et al, 1998;Millikan et al, 2000;Rossini et al, 2002 Caucasians c 2674 1064/2232 (47.7)* 448/2674 (16.7) 31 (9.3) Amer et al, 2011;Baranova et al, 1997;Chen et al, 1996;D'Alo et al, 2004;Gsur et al, 2001;Kargas et al, 2003;Millikan et al, 2000;Mitrunen et al, 2001;Steinhoff et al, 2000;Welfare et al, 1999 Asians 1). The frequency distribution of GSTM1 and GSTT1 alleles were compared between different states of India and other populations all over the world (Table 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, based on the latest statistics from GST-related studies after 2005, we expect further studies can involve more samples detected by different GST genotypes simultaneously in order to find out whether there were synergy effect among them. A third potentially important finding was that, in our assessment of the association between a GSTT1-null genotype and adults with gliomas, two independent studies by Coutinho et al (2010) and Ezer et al (2002) with weight contributions of 7.82% and 8.39% respectively, were statistically analyzed to determine that patients who carried the GSTT1 null genotype had no increased risk of developing gliomas (Figure 6). In addition, a similar phenomenon was not observed in the GSTM1 and GSTP1 polymorphism analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 6, sensitivity analyses of GST polymorphisms indicated that two independent studies by Coutinho et al (2010) and Ezer et al (2002), with weight contributions of 7.82% and 8.39%, respectively, were the main origin of the lack of significance in the analysis of association between a GSTT1-null genotype and adult gliomas. If these two studies were excluded, an association between a GSTT1-null genotype and glioma risk would be observed (pooled OR, 1.415; 95% CI, 1.121-1.786; P heterogeneity, 0.076; I square, 45.4%).…”
Section: Sensitivity Analysismentioning
confidence: 96%
See 1 more Smart Citation